The Influence of Green Product and Quality Perception on Buying Interest in Rattan Handicraft Products Evidence form South Barito Community - PEGGY AULIA EZRA YOLA (Jurnal Manajemen Sains dan Organisasi, 2025)
Objective – This study aims to examine the influence of green products and quality perception on consumer buying interest in rattan handicraft products in South Barito. The research background highlights increasing public concern for environmentally friendly products in response to environmental issues in Indonesia. Rattan handicrafts are recognized as sustainable products with cultural value and economic potential. Design/Methodology/Approach – This study applied a quantitative method with purposive sampling of 100 respondents who had purchased rattan handicrafts. Data were collected through questionnaires and analyzed using SPSS, including validity and reliability tests, classical assumption tests, and multiple linear regression. Findings – The findings indicate that both green product and quality perception positively and significantly affect consumer buying interest. Implications – This research provides practical implications for rattan craft entrepreneurs to maintain sustainability and product quality in order to strengthen consumer attraction and purchase intention, contributing to local economic growth and environmental preservation.